ANALISIS PERPUTARAN KAS, PERPUTARAN PIUTANG, DAN PERPUTARAN PERSEDIAAN DALAM MENINGKATKAN PROFITABILITAS PADA CV. PASIPA RAYA KOTA BAUBAU - Nunung Fitriani Ramli; Azaluddin; Nining Asniar Ridzal (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the role of cash turnover, receivables turnover, and inventory turnover in increasing profitability at CV. Pasipa Raya for the 2023-2025 period. The research method used is quantitative descriptive. The data used are secondary data in the form of financial statements obtained from the company and primary data from interviews with the financial manager. Data analysis result from CV. Pasipa Raya indicate that cash turnover in 2025 decreased. This decrease is a management strategy to increase liquidity as a measure to anticipate price increases from suppliers, not an indication of inefficiency. Receivables turnover increased significantly in 2025 driven by the effectiveness of the accounts receivable collection policy through sending payment reminders before the due date. Meanwhile, inventory turnover continued to decline until 2025 as a consequence of the bulk purchasing strategy to lock in prices. ROA experienced an increase from 2023 to 2025. This increase in profitability was more dominantly driven by the efficiency of Cost of Goods Sold and improved receivables management. Based on the analysis result, it is concluded that the increase in profitability of CV. PASIPA RAYA during the 2023-2025 period was not solely determined by the velocity of all current assets turnover, but also by the implementation of appropriate management strategies in facing market conditions.